Adjustment day - Palahniuk, Chuck (W. W. Norton & Company, 2018)
"Geriatric politicians bring the nation to the brink of a third world war to control the burgeoning population of young males, while working-class men dream of burying the elites. Adjustment Day's arrival makes real the logical conclusion of every separatist fantasy, alternative fact, and conspiracy theory lurking in the American psyche"--